Modified auxiliary boundary conditions method for an ill‐posed problem for the homogeneous biharmonic equation - Benrabah, Abderafik; Boussetila, Nadjib; Rebbani, Faouzia (Mathematical methods in the applied sciences, 2020)
In this paper, we are interested in the inverse problem for the biharmonic equation posed on a rectangle, which is of great importance in many areas of industry and engineering. We show that the problem under consideration is ill‐posed; therefore, to solve it, we opted for a regularization method via modified auxiliary boundary conditions. The numerical implementation is based on the application of the semidiscrete finite difference method for a sequence of well‐posed direct problems depending on a small parameter of regularization. Numerical results are performed for a rectangle domain showing the effectiveness of the proposed method.